Enhanced computed tomography features predict pancreatic neuroendocrine neoplasm with Ki-67 index less than 5%. Issue 147 (February 2022) - Yu, Haopeng; Li, Mou; Cao, Dan; Wang, Yi; Zeng, Ni; Cheng, Yue; Huang, Zixing; Song, Bin
Graphical abstract: Highlights: Key finding : Preoperative contrast enhanced computed tomography can help clinicians decide whether patients with nonmetastatic pancreatic neuroendocrine neoplasm are more eligible for curative surgery. Importance : Logistic regression revealed an area under the receiver operating characteristic curve of 0.853 for predicting nonmetastatic pancreatic neuroendocrine neoplasms with a Ki-67 index of < 5%. Abstract: Background: Several studies have suggested that patients with pancreatic neuroendocrine neoplasm (pNEN) with the Ki-67 index of < 5% are more likely to show better prognosis after clinical intervention. Moreover, the Ki-67 index at 5% has also been suggested as a potential threshold by the 2016 European Neuroendocrine Tumor Society guidelines. Objective: Based on preoperative enhanced computed tomography (CT), this study aimed to investigate imaging characteristics eligible to discriminate the ≤ 5% Ki-67 group from the > 5% Ki-67 group of patients with nonmetastatic pNEN. Methods: Patients with pathologically diagnosed pNEN and preoperative multiphase CT were enrolled. Their Ki-67 index was calculated and grouped according to the 5% cutoff value. The following CT imaging characteristics and some serum biomarkers were assessed between the two groups: the diameter, location, tumor margin, calcification, pancreatic atrophy, distal pancreatic duct dilation, vessel involvement, and enhancement pattern characteristics of both arterial phase (AP) and portal vein phase (PVP). Results: A total of 142 patients with pNEN were enrolled in this study, comprising 104 in the low (Ki-67, 1%–5%) and 38 in the high index group (Ki-67, >5%). Alpha fetoprotein and cancer antigen 125 were significantly different between the two groups (P-values, 0.030 and 0.049, respectively). The diameter (P < 0.0001), margin (P = 0.003), distal main ductal dilation (P = 0.021), vessel involvement (P = 0.002), AP hypoenhancement (P < 0.0001), PVP hypoenhancement (P = 0.003), AP ratio (P = 0.0001), and PVP ratio (P = 0.0003) were significantly different between the low and high index groups. The area under the curve of the multivariate logistic regression model was 0.853. Conclusion: Nonmetastatic pNENs with larger diameter, ill-defined margin, distal main ductal dilation, and tumor hypoenhancement in AP in preoperative enhanced CT tend to have a Ki-67 index of > 5%.The results of this study provide an alternative method to clinicians to decide whether surgery is appropriate.